Typische Lernschwierigkeiten mit Darstellungswechseln bei elementaren Funktionen: Welche Schwierigkeiten kennen Lehrkräfte und wie schätzen sie Aufgabenbearbeitungen ihrer Klassen ein? (mathematica didactica, 2020)
The aim of this study is to clarify the needs for a mathematics teacher training related to elementary functions. Therefore, we investigated among 80 students from grade 7 and 8 to what extent they struggled with learning difficulties with representational changes deduced from the literature. Furthermore, their mathematics teachers were interviewed to identify their corresponding knowledge. The data collection was done at the student level via paper-pencil tests and at the teacher level via structured guideline interviews. The results show that the learning difficulties deduced from the literature are also prevalent in this student sample with partly large class differences. Some of the documented learning difficulties were not known by the participating teachers, the quality of their estimations about their students’ performance proved to be heterogeneous. Implications of these findings are discussed with regard to theory and practice.